2007
DOI: 10.1103/physreva.75.032718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the final-state electron-ion interactions on the fully differential cross sections for heavy-particle-impact ionization of helium

Abstract: Three-dimensional fully differential cross sections for heavy-particle-impact ionization of helium are examined. Previously, the three-body distorted-wave ͑3DW͒ model has achieved good agreement with experiment in the scattering plane for small momentum transfers, but poor agreement for large momentum transfers. Poor agreement was also observed outside the scattering plane for all momentum transfers. In particular, the 3DW calculations predicted cross sections that were too small both perpendicular to the scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 17 publications
(1 reference statement)
3
27
0
Order By: Relevance
“…Over the last 10-15 years kinematically complete experiments (i.e., experiments which determine the momentum vectors of all particles in the system under investigation) revealed that the description of the spatial and temporal evolution of systems as simple as two positively charged ions interacting with an electron represent a formidable theoretical challenge [e.g., [1][2][3][4][5][6][7][8][9][10][11][12]. The basic problem is that the Schrödinger equation is not analytically solvable for more than two mutually interacting particles, even when the underlying forces are precisely known.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 10-15 years kinematically complete experiments (i.e., experiments which determine the momentum vectors of all particles in the system under investigation) revealed that the description of the spatial and temporal evolution of systems as simple as two positively charged ions interacting with an electron represent a formidable theoretical challenge [e.g., [1][2][3][4][5][6][7][8][9][10][11][12]. The basic problem is that the Schrödinger equation is not analytically solvable for more than two mutually interacting particles, even when the underlying forces are precisely known.…”
Section: Introductionmentioning
confidence: 99%
“…These findings initiated many sets of theoretical studies. For example, later studies [15] showed that an improved treatment of the electron-ion interactions had little effect on the distorted-wave calculations, and it was shown that the agreement between experiment and theory grew steadily worse as one moves from the coplanar to the perpendicular plane. A very recent study using an impact-parameter coupledpseudostate approximation [16] reported similar results to the earlier distorted-wave calculations, which is in good agreement with measurement in the coplanar geometry but poor agreement in the perpendicular plane.…”
Section: Introductionmentioning
confidence: 99%
“…The disagreement to experiment was particularly pronounced in fully quantum-mechanical calculations [e.g. [5][6][7][8], but amazingly if the interaction between the projectile and the target core (PI interaction) was treated classically or semi-classically good or at least improved agreement was achieved [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%